Un modelo biogeoquímico para el Golfo de Nicoya, Costa Rica - A. Tabash Blanco, Farid (2007)
In agreement with the Broecker and Penn two-boxes model, I generated a biogeochemical balance model for the Gulf of Nicoya (Guanacaste, Costa Rica) using two nutrient reservoirs: surface water and deep water. The mixing zone was located at a depth of 20 m. There is a balance between surface waters descending to the bottom and upwelling waters that carry nutrients and other chemical elements to the surface. The main source of nitrogen (nitrate), was the outlet of the Tempisque and Tárcoles rivers. The Gulf of Nicoya is a net source of Dissolved Inorganic Nitrogen (DIN) with an availability rate of 87 x 103 mol day-1 in the dry season and 3 044 x 103 mol day-1 in the rainy season. Dissolved Inorganic Phosphate (DIP) was estimated in 27 mol day-1 in the dry season and 207 mol day-1 in the rainy season. The dynamics of these biolimited nutrients, in relation to runoff seasonal variations, fits the bio-logical processes reported for the gulf, for example, for variations in primary productivity levels, and maturity and reproduction seasons for species with short and long life cycles.